Stosunek doświadczonych pracowników akademickich do młodych adeptów nauki w ujęciu Edwarda Marczewskiego: aspekt deontologiczny = The attitude of experienced academics towards young researchers according to Edward Marczewski: a deontological approach - Nowakowski, Piotr T. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author analyses the attitude of experienced academics towards young researchers. The title implies, and in particular mentioned deontological approach, that the article deals with the professional obligations of the former towards the latter. The obligations result from the existing regulations or from praxis. The principles formulated by Edward Marczewski, the famous Polish mathematician, served as the main point of reference in the article. It is important to mention the fact that not only did he articulate the principles, he also brought them into effect. The author also refers to the importance of Marczewski heritage in the contemporary deontological thought.
Keywords: Marczewski, Edward (polski matematyk; 1907-1976); pracownicy naukowi; środowisko akademickie; deontologia